Culture and understanding the role of feedback for health professions students: realist synthesis protocol. Issue 2 (21st February 2022) - Fullerton, Paul Douglas; Sarkar, Mahbub; Haque, Shamsul; McKenzie, Wendy
Abstract : Introduction: Clinical education has moved to a 'competency-based' model with an emphasis on workplace-based learning and assessment which, in turn, depends on feedback to be effective. Further, the understanding of feedback has changed from information about a performance directed to the learner performing the task, to a dialogue, which enables the learner to act and develop. In health professional education, feedback is a complex interaction between trainee, supervisor and the healthcare system. Most published research on feedback in health professional education originates in Europe and North America. Our interest is on the impact of C ulture on this process, particularly in the context of Asian cultures. The (scientific) realist approach of Pawson and Tilley provides a means to examine complex interventions in social situations, and thus is an appropriate lens to use for this study. This is a protocol for a realist synthesis which asks how, why and in what circumstances do Asian Cultures influence health professional trainees to seek, respond to and use feedback given in the clinical environment, if at all. Methods and analysis: An initial search was performed to help define the scope of the review question and develop our initial programme theory. The formal electronic search was carried out in February 2020 and included: CINAHL, ERIC, Medline and PsycInfo, and repeated in October 2020. Retrieved articles were imported into Covidence for screening and data extraction, after which components of the Context–Mechanisms–Outcomes configurations will be sought to refine the initial programme theory. Ethics and dissemination: As this study is a literature review, ethics approval is not required. The findings will be documented in line with the RAMESES (Realist And MEta-narrative Evidence Syntheses: Evolving Standards) publications standards for Realist syntheses, and we plan to disseminate the findings by means of a peer-reviewed journal article and conference presentation(s).